Plasma exchange therapy in sepsis - Nguyen, Trung C.; Han, Yong Y.; Fortenberry, James D.; Carcillo, Joseph A. (Journal of Pediatric Infectious Diseases, 2009)
Sepsis is a systemic inflammatory syndrome in response to an infection. With the current resuscitation practice, up to 16% of children with severe sepsis and septic shock still progress to develop multiple organ failure (MOF), a condition that is associated with poor outcome. In this review, we focus on the thrombotic microangiopathic paradigm for the development of sepsis-induced MOF. We describe the clinical observations, emerging experimental and laboratory evidence supporting the concept that sepsis-induced MOF may be a secondary thrombotic microangiopathy, manifest as thrombocytopenia-associated MOF. Drawing the pathologic similarities such as a disintegrin and metalloprotease with thrombospondin motifs-13 deficiency, impaired ultra-large von Willebrand factor multimers proteolysis, and von Willebrand factor-rich microthrombi and therapeutic success with plasma exchange in treating thrombotic thrombocytopenic purpura, a primary thrombotic microangiopathy, we propose a rationale for the role of plasma exchange therapy for sepsis and thrombocytopenia-associated multiple organ failure.
Keywords: Sepsis; ADAMTS-13; von Willebrand factor; thrombocytopenia; multiple organ failure; plasma exchange; thrombotic microangiopathy; TAMOF